2020
DOI: 10.1002/pssb.202000300
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Stresses in Rectangular Auxetic Membranes

Abstract: Auxetic materials exhibit a negative Poisson's ratio. Herein, the performance of rectangular auxetic membranes, under uniform load, is evaluated in terms of the maximum stress encountered. To facilitate convenient calculation, empirical modeling is conducted on the exact solution to reproduce displacement coefficients that are sufficiently accurate. A dimensionless maximum stress is then introduced to allow the effect from the membrane's Poisson's ratio and aspect ratio to be directly observed. Results reveal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 115 publications
(130 reference statements)
0
4
0
Order By: Relevance
“…Novel fabrics with auxetic properties [28,29,30,31], targeted for personal applications have been developed. Alongside the experimental studies, new theoretical models exhibiting negative Poisson's ratio [32,33,34,35,36,37,38,39,40,41,42,43,44,45,46] have been proposed. The search for the negative Poisson's ratio in known and naturally occurring materials revealed that around 70% of metals with cubic symmetry have such properties [47].…”
Section: Introductionmentioning
confidence: 99%
“…Novel fabrics with auxetic properties [28,29,30,31], targeted for personal applications have been developed. Alongside the experimental studies, new theoretical models exhibiting negative Poisson's ratio [32,33,34,35,36,37,38,39,40,41,42,43,44,45,46] have been proposed. The search for the negative Poisson's ratio in known and naturally occurring materials revealed that around 70% of metals with cubic symmetry have such properties [47].…”
Section: Introductionmentioning
confidence: 99%
“…[19,20] In this work, we use the more recent classification [20] which distinguishes between nonauxetics, partial auxetics, and auxetics. Vast potential applications of auxetic materials drive the theoretical and experimental investigations, which branch into auxetic metamaterials, [21][22][23][24][25][26][27][28] models, [16,[29][30][31][32][33][34][35][36][37][38][39][40][41] structures, [42][43][44][45][46][47][48] polymers, [49,50] composites, [51] foams, [52][53][54] and fabrics. [55][56][57][58] Most of the research on auxetics is focused either on developing new materials or searching for auxetic properties in existing ones.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical metamaterials [1][2][3][4] are a class of novel materials that exhibit their effective properties due to their rational design rather than the chemical composition. Based on their structure, these systems can exhibit counterintuitive mechanical properties such as negative Poisson's ratio (auxetic behaviour) [1,2,[5][6][7][8][9][10][11][12][13][14], negative stiffness [15][16][17][18][19][20] or negative compressibility [21][22][23][24][25]. In recent years, a continuous growth of the metamaterials research field led to their implementation in the case of superior biomedical [26,27] and protective devices [28,29].…”
Section: Introductionmentioning
confidence: 99%